Peptide mass mapping in bioapatites isolated from animal bones - Smrhova, Tereza; Junkova, Petra; Kuckova, Stepanka; Suchy, Tomas; Supova, Monika (Journal of materials science. Materials in medicine, 2020)
Bioapatite ceramics produced from biogenic sources provide highly attractive materials for the preparation of artificial replacements since such materials are not only more easily accepted by living organisms, but bioapatite isolated from biowaste such as xenogeneous bones also provides a low-cost material. Nevertheless, the presence of organic compounds in the bioapatite may lead to a deterioration in its quality and may trigger an undesirable immune response. Therefore, procedures which ensure the elimination of organic compounds through bioapatite isolation are being subjected to intense investigation and the presence of remaining organic impurities is being determined through the application of various methods. Since current conclusions concerning the conditions suitable for the elimination of organic compounds remain ambiguous, we used the mass spectrometry-based proteomic approach in order to determine the presence of proteins or peptides in bioapatite samples treated under the most frequently employed conditions, i.e., the alkaline hydrothermal process and calcination at 500 °C. Since we also investigated the presence of proteins or peptides in treated bioapatite particles of differing sizes, we discovered that both calcination and the size of the bioapatite particles constitute the main factors influencing the presence of proteins or peptides in bioapatite. In fact, while intact proteins were detected even in calcinated bioapatite consisting of particles >250 µm, no proteins were detected in the same material consisting of particles <40 µm. Therefore, we recommend the use of powdered bioapatite for the preparation of artificial replacements since it is more effectively purified than apatite in the form of blocks. In addition, we observed that while alkaline hydrothermal treatment leads to the non-specific cleavage of proteins, it does not ensure the full degradation thereof.
Keywords: Cattle; Tissue Engineering; Collagen Type I; Temperature; kosti a kostní tkáň; Femur; Particle Size; Apatites; Organic Chemicals; skot; kolagen typu I; organické látky; Mass Spectrometry; proteomika; tkáňové inženýrství; Animals; biokompatibilní materiály; zvířata; velikost částic; Ceramics; keramika; Pressure; Peptides; tlak; peptidy; femur; apatity; hmotnostní spektrometrie; teplota; Proteomics; Bone and Bones; Biocompatible Materials